Blockchain technology in supply chain management : Innovations, applications, and challenges - Kumar, Narendra; Kumar, Krishna ; 0000-0002-7196-0792; Aeron, Anurag; Verre, Filippo (Telematics and Informatics Reports, 2025)
Blockchain technology is emerging as one of the most transformative forces to have ever reshaped supply chain management, with unique transparency, security, and efficiency. This paper reviews the literature on blockchain technology and applications in core industries such as transportation, manufacturing, food and beverages, and healthcare. At its core, blockchain deploys distributed ledger technology to provide tamper-proof, secure record-keeping, enhancing traceability and provenance verification for complex supply chains. Smart contracts, IoT connectivity, and decentralized financial services allow blockchain to address its most critical challenges, including counterfeiting, supplier management, and the enforcement of sustainable and responsible sourcing practices. However, widespread adoption of blockchain in supply chains is inhibited by severe issues like scalability, interoperability, regulatory uncertainty, and lack of standardization. Additionally, the environmental impact of blockchain, i.e., the energy-intensive proof-of-work mechanisms is examined, along with potential strategies for mitigation. As the technology continues to evolve, the integration of artificial intelligence and 5G networks will further reshape supply chain management, unleashing new efficiencies and capabilities.
Publisher Copyright: © 2025
Keywords: Blockchain technology; Cybersecurity; Decentralized systems; Energy efficiency; Healthcare; Supply chain management